The effectiveness of various robotic technologies in assisting older adults. (September 2019) - Shishehgar, Majid; Kerr, Donald; Blake, Jacqueline
There is concern about the expanding size of the ageing population and burgeoning care costs for older adults. Robotic technology could assist older adults. In this study, the effectiveness of the robotic technologies is evaluated. A systematic literature review was undertaken of peer-reviewed literature. An initial set of 8533 studies was evaluated for relevance; these were reduced to a final subset of 58 studies finally subjected to analysis. This study categorised the problems encountered by older adults, identified robot types deployed to overcome them and derived a subjective effectiveness score. The most used and most effective robots were companion robots followed by telepresence robots. The findings imply positive effects of robotic technologies in helping elderly people's problems. Although robotic technologies could bring some innovation into aged care, more research is needed to design and develop robots to be of assistance and support elderly in having an independent lifestyle.